Football analytics 2021. The role of context in transferring analytics to the pitch (Barca Innovation Hub, 2020)
1.Always think before computing! 2. Unifying player IDs for the future of football analytics 3. Effects of situational variables on match statistics in elite football 4. How does context affect player performance in football? 5. Structure in football: putting formations into context 6. Defensive organisation disruption for team success 7. Reorganising around the ball in locational play: dynamic and multidirectional rebalancing 8. Ball positioning as key to understanding collective behaviour 9. Beyond `blind` distance covered in football match analysis: is it time to progress to a contextualised paradigm?